The Allocation of Talent to Financial Trading versus Production: Welfare and Employment Effects of Trading in General Equilibrium - Lutz Georg Arnold; Lutz Arnold; Sebastian Zelzner (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We incorporate occupational choice between finance and entrepreneurship into the Grossman-Stiglitz (1980) noisy rational expectations equilibrium model. Sophisticated agents produce output and create jobs as entrepreneurs or contribute to informational efficiency in financial markets as informed traders. Finance possibly attracts too much talent, for instance if the amount of noise in the economy is small, so that the asset price at a rational expectations equilibrium is highly informative anyway. The main beneficiaries of the allocation of talent to entrepreneurial activity are workers, whose wage and employment prospects improve when more sophisticated agents choose to become entrepreneurs.
Keywords: G14; J24; D61; 330